Interactions Between Gut Microbiota and Acute Childhood Leukemia - Wen, Yuxi; Jin, Runming; Chen, Hongbo (Frontiers in Microbiology, 2019)
Childhood leukemia, the commonest childhood cancer, is mainly consisted of acute lymphoblastic leukemia(ALL) and acute myeloid leukemia(AML). Though great progresses have been made in the survival rates of childhood leukemia, the long-term health problems of childhood leukemia survivors are remained remarkable. And the deep links between risk factors and childhood leukemia are in great need to be elucidated. What can be done to improve the prevention and the prognosis of childhood leukemia is an essential issue. Gut microbiota, referred to as one of the largest symbiotic microorganisms that accommodated in the gastrointestinal tract of human or animals, is found to be involved in the progression of various diseases. It is reported that microbiota may keep people in good health by participating in metabolism processes and regulating the immune system. Studies have also explored the potential relationships between gut microbiota and childhood leukemia. This review is meant to illustrate the roles of gut microbiota in the onset of acute childhood leukemia, as well as in the progress and prognosis of leukemia and how the treatments for leukemia affect gut microbiota. Besides, this review is focused on the possibility of building or rebuilding a healthy gut microbiota by adjusting the diet construction so as to help clinicians to deal with childhood leukemia.